Growth Organizational Culture on Hospital Performance Mediated by Person–Organization Fit and Job Satisfaction - Agustina Setyaningrum; Dewi Sri Surya Wuisan (Sarana Ilmu Indonesia (Salnesia), 2026)
Achieving optimal hospital performance requires management to align organizational culture with employee characteristics, with leadership serving as a strategic guiding mechanism. This study explored organizational leadership as a control variable influencing these relationships at Rumah Sakit Pelabuhan Palembang. This study aims to provide strategic insights for management to enhance performance through effective organizational culture management, person-organization fit, and increased employee job satisfaction.The population in this study was all staff, both health workers and non-health workers who worked at Rumah Sakit Pelabuhan Palembang during the period October to November 2024. This study involved 170 staff with a medical background (doctors) of 58 people, nurses 61 people, other health workers 36 people, and non-medical staff of 15 people. The sample selection technique used in this study was a purposive sampling approach, also known as judgmental sampling. Data was collected by distributing questionnaires containing 35 questions with a Likert Scale of 1-5. The data were analyzed using the SEM PLS method. Based on the results of this study, growth organizational culture positively influenced hospital performance, job satisfaction, and Person–Organization Fit. Also, organizational leadership affected hospital performance. The findings of this study could provide significant managerial implications for hospital management to make several continuous improvement, especially concerning aspects of human resource development and organizational culture.